Association of telomere length with chronic exposure to ionizing radiation among inhabitants of natural high background radiation areas of Ramsar, Iran - Movahedi, Anahita; Mostajaboddavati, Mojtaba; Rajabibazl, Masoumeh; Mirfakhraie, Reza (International Journal of Radiation Biology, 2019)
Purpose: There are few areas in the world where ionizing radiation (IR) dose received by the public from radon gas and other radioactive elements are much higher than recommended limits. Telomere length is a potential biomarker of genomic instability due to oxidative stress from IR exposure. In this study, we investigated the impact of chronic exposure to environmental IR on relative telomere length (RTL) in white blood cells (WBC) among inhabitants of high background radiation areas (HBRA) of Ramsar, Iran. Materials and methods: One hundred and four individuals from HBRAs of Ramsar and 104 age-matched subjects from normal background radiation areas (NBRA) of Iran were enrolled in the study. The RTLs of WBC DNA samples were measured by a quantitative polymerase chain reaction (q-PCR) approach. Results: Mean RTL in HBRA and NBRA groups did not show any significant difference (1.21 ± 0.71 versus 1.22 ± 0.66, p = .306). After controlling for all demographic variables, less than 1% of the variances in RTL values were related to background radiation exposure. Conclusion: We conclude that chronic exposure to natural IR has no statistically significant effect on RTL among the inhabitants of HBRAs of Ramsar compared with a control grou
Keywords: Ramsar; natural background radiation; relative telomere length; radon